Aula invertida como estrategia didáctica para fortalecer el aprendizaje de Estudios Sociales, unidad 1: Conquista y colonización de América, en los estudiantes de noveno año de EGB - Villafuerte Villacrés, Jesús Sebastián (2022)
In the investigation, the main objective is to create the inverted classroom as a didactic strategy, to strengthen the learning of the ninth grade EGB students in Unit 1: Conquest and colonization of America, of the Social Studies subject, and through didactic strategies. Innovative methodologies of the inverted classroom improve meaningful and collaborative learning, a methodology has been used, with a mixed approach, that is, qualitative and quantitative within a unique and coherent methodological perspective, which would allow a level of understanding of the research object, with a design of non-experimental research, the type of study was documentary or bibliographic, taking as a universe the population of ninth-year EGB students and teachers in the area of Social Sciences, the online survey and interview were used as a technique. to academic actors. The flipped classroom model is a pedagogical strategy that is used for the teaching- learning process through the internet, with different programs such as a dynamic video in PowToon, Video Scribe, gamification such as a random question roulette, the Tik Tok platform, the Edpuzzle software where audio notes were introduced, closed and open questions that can be answered in the same way with audio, a game related to the topic that the student can copy and paste in the browser, also a YouTube video that helped to know the contents, the results in the students were positive because it is based on Piaget's constructivist didactic methodology and currently adding technological tools to this technique is known as inverted classroom that motivates the student to be a collaborative, participatory and cooperative entity. this way to achieve meaningful learning